2020
DOI: 10.3390/math8111887
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Important Factors for Bleeding in Liver Cirrhosis Disease Using Ensemble Data Mining Approach

Abstract: The main motivation to conduct the study presented in this paper was the fact that due to the development of improved solutions for prediction risk of bleeding and thus a faster and more accurate diagnosis of complications in cirrhotic patients, mortality of cirrhosis patients caused by bleeding of varices fell at the turn in the 21th century. Due to this fact, an additional research in this field is needed. The objective of this paper is to develop one prediction model that determines most important factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…From other site from planed research in technique and methodology for solving considered healthcare problem and problems in healthcare which already was subject of research of authors [114,115] authors will deal in feature with other from many different problems in healthcare and other fields of human life as for example traffic and education which the authors have already done [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…From other site from planed research in technique and methodology for solving considered healthcare problem and problems in healthcare which already was subject of research of authors [114,115] authors will deal in feature with other from many different problems in healthcare and other fields of human life as for example traffic and education which the authors have already done [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, various ensemble models previously published by the coauthors of this study can be found in references [114][115][116][117][118]. These models employ diverse strategies such as maximum voting or triple modular redundancy, combined with various classification and machine learning (ML) algorithms, to address a range of problems in human life.…”
mentioning
confidence: 99%
“…This issue contains the successful invited submissions [1][2][3][4][5][6][7][8][9][10][11] to a Special Issue of Mathematics on the subject area of "Dynamics under Uncertainty: Modeling Simulation and Complexity".…”
mentioning
confidence: 99%
“…Li et al [4] investigated the problems of state feedback and the static output feedback preview controller for uncertain discrete-time multiple-input multiple-output The geographical distribution of the authors (published papers) is presented in Table 1. Published submissions are related to road traffic risk analysis [1], dual-rotor systems [2], multi-criteria decision making [3,5,6,8,9], MIMO discrete-time systems [4], the classification and diagnosis of brain disease [7], data mining [10], and empathic building [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation